Strengthening Religious Moderation through Religious Education Based on Local Wisdom of Pesantren in Madura and the Tapal Kuda Region - Syarif, Zainuddin; Abdul Mukti Thabrani,; Imamuddin, (TADRIS: Jurnal Pendidikan Islam, 2025)
This study examines strengthening religious moderation through religious education based on the local wisdom among the Pesantren in Madura and Tapal Kuda regions. This study is a field study conducted based on qualitative research. Based on the analysis of field data, this study found that strengthening religious moderation through local wisdom values ​​of pesantren in Madura and the Tapal Kuda region requires three elements, namely the existence of kiai, santri, and alumni, along with their social networks. These three elements are inseparable from Islamic boarding school life in educational activities and preaching. In strengthening religious moderation, all three play central and strategic roles and functions. They generally carry out these roles and functions in two approaches at once. First, the structural approach is carried out by strengthening moderation at the institutional level, in this case, education, and implementing teaching activities. Second, the cultural approach that strengthens religious moderation among pesantren in Tapal Kuda is carried out through cultural methods. The artistic process in question includes two things, namely religious understanding, and rituals in pesantren, where the majority of religious paradigms among pesantren in the Tapal Kuda region of Madura adhere to the knowledge of Ahlu sunah wal jamaah an-Nahdliyyah.